Yeasts Biodiversity and Its Significance: Case Studies in Natural and Human-Related Environments, Ex Situ Preservation, Applications and Challenges - Barriga, Enrique Javier Carvajal; Libkind, Diego; Briones, Ana Isabel; Iranzo, Juan Úbeda; Portero, Patricia; Roberts, Ian; James, Steve; Morais, Paula B.; Rosa, Carlos A. (IntechOpen, 2011)
None